PROBLEMATIKA PEMBELAJARAN SEJARAH KEBUDAYAAN ISLAM PADA PESERTA DIDIK KELAS III DI MI MUHAMMADIYAH NUNU KEC. TATANGA KOTA PALU - Hikmatullah, Hikmatullah; Rusli Takunas; Andi Anirah (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2024)
Problems of learning Islamic Cultural History (SKI) for class III students at MI Muhammadiyah Nunu District. Palu City Tatanga is a problem with students' interest in reading, memorizing and remembering material, lack of interest and motivation. The problems for teachers are teacher preparation before the learning process, learning media, learning methods, and SKI learning outcomes. Efforts/solutions made to overcome these learning problems are increasing students' interest in reading, providing motivation, using interesting media and methods, as well as SKI learning outcomes in the form of carrying out remedial measures. The implication of this research is for all educators who have the ability to continue to provide the best lessons to students to improve the learning process and provide the necessary facilities and infrastructure to support the learning process at MI Muhammadiyah Nunu District. Tatanga, Palu City, so that the learning process of Islamic Cultural History (SKI) runs better.